Awareness towards osteoporosis among patient’s female relatives in orthopaedic wards at Hospital Universiti Sains Malaysia (Hospital USM) - Zainudin, Nur Anisah (Universiti Sains Malaysia, 2016)
The level of awareness towards Osteoporosis is still low. The purpose for this crosssectional study is to determine the level of awareness towards Osteoporosis among patient’s female relatives in orthopaedic wards. This study also examined the differences between the level of awareness and the level of education as well as determined the relationship between age and the level of awareness. The subjects included 94 patient’s female relatives in the three orthopaedic wards at Hospital USM. They were selected using convenience sampling. Data were collected from December 2015 until February 2016 using Osteoporosis Prevention and Awareness Tool (OPAAT). The data were analysed using SPSS version 22.0 for mean, standard deviation, frequency, percentage, /2-value and r-value. Ethical approval was obtained from Research Ethics Committee (Human), USM. The overall awareness level towards Osteoporosis among patient’s female relatives was low (Af=14.95, SD=5A73). The majority of the female relatives got low awareness on the Osteoporosis in general (AY=4.87, 5D=2.324), consequences of Osteoporosis (Af=2.68, 50=1.255) and Osteoporosis prevention (A/=7.41, 50=3.303). The study found that there were significant differences between the level of education and the level of awareness among the female relatives with P = 0.017. Finally, there is positive but weak relationship between the age and the level of awareness among the female relatives with r = 0.027. Action should be taken to increase the awareness towards Osteoporosis among female relatives. In order to make sure the programme is effective, proper planning for health educational programme on Osteoporosis should be done. The expert health practitioner should be assigned so that the programme is beneficial.